Observaciones sobre ensambles de aves de un bosque insular del Rio Paraná Medio, Argentina - BELTZER, ADOLFO H.; Ordano, Mariano (Revista Ceres, 2015)
Riparian forests are important ecological units of fluvial systems. Diversity, richness, trophic groups, relative importance of the species and habitat use were described in three different strata of an insular forest Every month during 1988 (except April), sighting and hearing birds were recorded in the morning on three line transects of 150 meters each, during 30 minutes. Twenty four species were recorded with d:versity end richness being nearby constant around the year. Major trophic groups were insectivorous and omnivorous, and bird species with highest relative importance in the assemblage were Furnarius rufus, Phacellodomus striaticollis, Polioptila dumicola, Pitangus sulphuratus, Turdus rufiventris, Paroaria capitata, Saltator caenrles cens and Cacicus solitarius. Middle and lower strata were the most use(t P. capitata was observed only in the upper stratum, while Chiorostilbon aureoventris, Phacellodomus rub, P striaticollis and T. rufiventris were observed only in tie lower and middle strata.